LITERATURE REVIEW: PENGARUH PENERAPAN SISTEM PEMBELAJARAN ADAPTIF BERBASIS AI TERHADAP HASIL BELAJAR DAN MOTIVASI BELAJAR - Haidar Triari Respati (Prosiding Seminar Nasional Indonesia, 2026)
Adapting teaching strategies to students' varied requirements is one of the biggest difficulties facing education today.  Through the use of adaptive learning systems, which enable learning materials to be customized in real-time to students' strengths, shortcomings, and learning pace, artificial intelligence (AI) technology offers a creative answer.  By offering a more individualized learning experience, this approach may enhance student motivation and learning outcomes.  The purpose of this study is to examine how learning results and learning motivation are affected by the use of an AI-based adaptive learning system. This study looks at several current studies on the application of AI in education, especially in the context of adaptive learning, using the Literature Review (LR) method.  The findings demonstrate that using an AI-based adaptive learning system significantly improves student motivation and learning outcomes.  However, in order for the advantages of this technology to be felt equally across all educational levels, concerns pertaining to the disparity in access to technology and the preparedness of educators to use AI still need to be resolved.